2016
DOI: 10.1242/jcs.179374
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin D and its newly identified transport receptor SEZ6L2 can modulate neurite outgrowth

Abstract: How, in the absence of a functional mannose 6-phosphate (Man-6-P)-signal-dependent transport pathway, some acid hydrolases remain sorted to endolysosomes in the brain is poorly understood. We demonstrate that cathepsin D binds to mouse SEZ6L2, a type 1 transmembrane protein predominantly expressed in the brain. Studies of the subcellular trafficking of SEZ6L2, and its silencing in a mouse neuroblastoma cell line reveal that SEZ6L2 is involved in the trafficking of cathepsin D to endosomes. Moreover, SEZ6L2 can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 52 publications
2
51
0
Order By: Relevance
“…Statistical analyses were done with a 1-way ANOVA with Tukey's posttest; *P < 0.05. double-KO mice compared with WT mice, PERK-KO mice, and ATF6α-KO mice at P28, and in the optic nerve of double-KO mice compared with WT mice and PERK-KO mice at P45, but were not decreased at P21. Both SEZ6L2 and GNPTAB participate in the transport of the lysosomal hydrolase cathepsin D from the trans-Golgi network to the lysosome (40)(41)(42)(43). We further assessed the subcellular localization of cathepsin D in oligodendrocytes of these mice.…”
Section: Inactivation Of Perk and Atf6α In Oligodendrocytes Caused Lamentioning
confidence: 99%
“…Statistical analyses were done with a 1-way ANOVA with Tukey's posttest; *P < 0.05. double-KO mice compared with WT mice, PERK-KO mice, and ATF6α-KO mice at P28, and in the optic nerve of double-KO mice compared with WT mice and PERK-KO mice at P45, but were not decreased at P21. Both SEZ6L2 and GNPTAB participate in the transport of the lysosomal hydrolase cathepsin D from the trans-Golgi network to the lysosome (40)(41)(42)(43). We further assessed the subcellular localization of cathepsin D in oligodendrocytes of these mice.…”
Section: Inactivation Of Perk and Atf6α In Oligodendrocytes Caused Lamentioning
confidence: 99%
“…Until now, the function of SEZ6L2 was poorly understood; however, studies have begun to reveal some of its basic functions. A previous study by Boonen et al suggested that SEZ6L2 is involved in the trafficking of cathepsin D to endosomes, and hence modulates neurite outgrowth. SiRNA‐mediated down‐regulation of SEZ6L2 prevents phosphorylation of adducin and neuritogenesis .…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that mice deficient in SEZ6L2 suffer from motor ataxia, impaired cognition and abnormal neuronal innervation (a disturbance of the cerebellar synaptic maturation in mutant mice lacking BSRPs, a novel brain‐specific receptor‐like protein family) . Cleavage of SEZ6L2, which is mediated by cathepsin D, induces neurite outgrowth . In one patient suffering from cerebellar ataxia and retinopathy, anti‐SEZ6L2 antibodies were detected, which were also associated with progressive cerebellar ataxia .…”
Section: Introductionmentioning
confidence: 99%
“…The morphology of subcellular structures wherein they reside remains invisible. Conversely, electron microscopy (EM) enables observations at nanometre‐scale resolution and is therefore often employed to gain ultrastructural characterization of the subcellular environment pertinent to the biomolecules initially investigated with FM (Predescu et al ., ; Robenek et al ., ; Sarnataro et al ., ; Choi et al ., ; Boonen et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Tel: +31-71-5269294; e-mail: a.j.koster@lumc.nl olution and is therefore often employed to gain ultrastructural characterization of the subcellular environment pertinent to the biomolecules initially investigated with FM (Predescu et al, 2003;Robenek et al, 2006;Sarnataro et al, 2009;Choi et al, 2015;Boonen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%